(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
One of the most effective tools in the development of the market mechanism is the system of tax incentives aimed at reducing the tax burden on economic entities, for which it is necessary to improve the taxation mechanism and minimize the negative internal and external factors affecting it.